From Fry Pan to Fire or From Fire to Fry Pan: A Comparative Critique of Competency of a Child Witness in Nigeria (Global Journal of Human-Social Science, 2014)
This paper takes a comparative critique of the Nigerian Evidence Acts 2004 and its 2011 counterpart. Specifically, the paper seeks to tackle the question whether the controversial issues raised against the provisions on competency of a child witness under the 2004 Act have been resolved or they are still rearing their ugly heads under the 2011Act. In tackling this question, the paper relies on the two Evidence Acts as the major statutes. Other domestic legislation of Nigeria relevant for consideration, include the Children and Young Persons Act, the Criminal Procedure Act, the Child Rights Act and the Constitution of Nigeria, (as amended). At the international plane, the Convention on the Rights of the Child, Convention on the Elimination of Discrimination against Women, the African Charter on the Rights and Welfare of the Child and the Protocol on the Rights of Women in Africa are relevant.